Read Opportunities for Building Business Performance in West Java - Hermina, Nurul; Firdaus, Erwin (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2023)
The aim of this research is to investigate the impact of business opportunities on the business performance of MSME business actors in West Java after the pandemic. The sample used was 123 MSMEs in West Java. This research uses PLS for data analysis. The research results show that business opportunities can improve business performance in West Java. The results of this research have important implications because they show that understanding and exploiting business opportunities can make a positive contribution to the performance of MSMEs in West Java after the pandemic. This provides valuable insight for MSME players and related stakeholders in designing strategies and policies that support regional economic growth through developing a competitive MSME sector. These findings can be an important basis in supporting the development of MSMEs and regional economic recovery, underscoring the importance of opportunity-based strategies in facing economic and environmental changes.